Peluang Kerja Penyandang Disabilitas di Kota Metro - Sunarwan, Aisyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2021)
Getting a job is something that everyone really wants without exception for people with physical disabilities. In Metro, there are many people with physical disabilities who do not or have not gotten a job so they do anything to survive. This study was conducted to determine employment opportunities for people with physical disabilities based on the Law of the Republic of Indonesia Number 8 of 2016 article 53. Data in this study were obtained through observation and interview process to the heads of agencies and people with physical disabilities in Metro. Based on the results of the analysis of the data obtained, it can be concluded that the job opportunities for persons with physical Disabilities in Metro are still relatively low and the rights to obtain employment for persons with disabilities as stipulated in the Act are still not well realized.